Sayles Jenks Bowen papers - Bowen, Sayles Jenks, 1813-1896.
Correspondence, business papers, and legal papers. Subjects include the elections of 1876 and 1880, the presidential administration of Rutherford Birchard Hayes, political support for Chester Alan Arthur, James Gillespie Blaine, and James A. Garfield, and opposition to Ulysses S. Grant. Correspondents include James Gillespie Blaine, William E. Chandler, Frederick Douglass, Reuben E. Fenton, Robert Todd Lincoln, James H. Platt, and Whitelaw Reid.
Public official and mayor of Washington, D.C.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Arthur, Chester Alan, -- 1829-1886.; Blaine, James Gillespie, -- 1830-1893.; Blaine, James Gillespie, -- 1830-1893 -- Correspondence; Chandler, William E. -- 1835-1917 -- Correspondence; Douglass, Frederick, -- 1818-1895 -- Correspondence; Fenton, Reuben E. -- 1819-1885 -- Correspondence; Garfield, James A. -- 1831-1881.; Grant, Ulysses S. -- 1822-1885.; Hayes, Rutherford Birchard, -- 1822-1893.; Lincoln, Robert Todd, -- 1843-1926 -- Correspondence; Platt, James H., -- 1837-1894 -- Correspondence; Reid, Whitelaw, -- 1837-1912 -- Correspondence; Elections -- United States -- 1876.; Elections -- United States -- 1880.; United States -- Politics and government -- 19th century; Mayors -- Washington (D.C.); Public officials